Synthesis of novel alkynyl imidazopyridinyl selenides: copper-catalyzed tandem selenation of selenium with 2-arylimidazo[1,2-a]pyridines and terminal alkynes - Matsumura, Mio; Tsukada, Kaho; Sugimoto, Kiwa; Murata, Yuki; Yasuike, Shuji (Beilstein Journal of Organic Chemistry, 2022)
Alkynyl selenides have attracted considerable research interest recently, owing to their applications in the biological and pharmaceutical fields. The Cu-catalyzed tandem reaction for the synthesis of novel alkynyl imidazopyridinyl selenides is presented. A one-pot synthesis route afforded alkynyl imidazopyridinyl selenides in moderate to good yields. This was achieved by a two-step reaction between terminal alkynes and diimidazopyridinyl diselenides, generated from imidazo[1,2-a]pyridines and Se powder, using 10 mol % of CuI and 1,10-phenanthroline as the catalytic system under aerobic conditions. The C(sp2)–Se and C(sp)–Se bond-formation reaction can be performed in one-pot by using inexpensive and easy to handle Se powder as the Se source. The reaction proceeded with terminal alkynes having various substitutions, such as aryl, vinyl, and alkyl groups. The obtained alkynyl imidazopyridinyl selenide was found to undergo nucleophilic substitution reaction on Se atom using organolithium reagents and 1,3-dipolar azide–alkyne cycloaddition based on the alkyne moiety.
Keywords: alkynyl imidazopyridinyl selenide; copper catalyst; imidazo[1,2-a]pyridine; selenium; tandem reaction; terminal alkyne